2010
DOI: 10.1126/scisignal.2001195
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Domain of Fibroblast Growth Factor Receptor 3 Inhibits Ligand-Independent Dimerization

Abstract: Dysregulation of ligand-independent receptor tyrosine kinase (RTK) dimerization, which is the first step in RTK activation, leads to pathologies. A mechanistic understanding of the dimerization process is lacking, and this lack of basic knowledge is one bottleneck in developing effective RTK-targeted therapies. For instance, the roles and the relative contributions of the different RTK domains to RTK dimerization are unknown. Here we use quantitative imaging Förster resonance energy transfer (QI-FRET) to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(116 citation statements)
references
References 66 publications
4
112
0
Order By: Relevance
“…47 It has also been shown in another system, fibroblast growth factor receptor 3, that the ECD prevents ligand-independent receptor dimerization, thereby avoiding constitutive receptor signaling. 48 The ITC data presented herein for VEGFR-2 specify the distinct roles of individual extracellular subdomains in ligand-mediated dimerization; ECD subdomains 2 and 3 form the high-affinity ligand-binding site, whereas the energetically unfavorable homotypic interactions in domains 4-7 reduce the overall binding affinity. Tao et al showed previously that deletion of D4-7 led to constitutive ligand-independent receptor activation.…”
Section: Discussionmentioning
confidence: 76%
“…47 It has also been shown in another system, fibroblast growth factor receptor 3, that the ECD prevents ligand-independent receptor dimerization, thereby avoiding constitutive receptor signaling. 48 The ITC data presented herein for VEGFR-2 specify the distinct roles of individual extracellular subdomains in ligand-mediated dimerization; ECD subdomains 2 and 3 form the high-affinity ligand-binding site, whereas the energetically unfavorable homotypic interactions in domains 4-7 reduce the overall binding affinity. Tao et al showed previously that deletion of D4-7 led to constitutive ligand-independent receptor activation.…”
Section: Discussionmentioning
confidence: 76%
“…There have been previous attempts to use FRET to study FGFR dimerization in the context of plasma membrane (25,54,55). Because our approach utilizes non-cell-permeable fluorescent probes, it enabled a FRET-based approach to study FGFR interactions specifically on the cell surface in the context of physiological membrane environment and in the presence of intracellular scaffolding proteins that might affect FGFR dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not only the ECD but also other parts of FGFR1 may have propensity to dimerize. Dimerization of isolated TMD in liposomes has been observed (24,25), and TKD could also contribute to receptor dimerization via interaction with intracellular signaling proteins (26,27). Indeed, very little is known about the cell surface dynamics of full-length FGFRs.…”
Section: Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The A206K mutation was introduced in eYFP to render it monomeric. The gene encoding EphA2 was subcloned between the HindIII and KpnI restriction sites in the pcDNA 3.1(ϩ) vector, which already contained a sequence encoding a 15-amino acid linker, followed by either mTurq or eYFP (30). Polymerase chain reaction (PCR) of the EPHA2 gene was performed using 5Ј-GGGC-CCAAGCTTACCAGCAACATGGAGCTCCAGGCAGCC-3Ј as a forward primer and 5Ј-CCCGGGGGTACCTTTGAT-GGGGATCCCCACAGTGTTCAC-3Ј as a reverse primer.…”
Section: Epha2mentioning
confidence: 99%